Sistem Pendukung Keputusan Pemilihan Pegawai Honorer Kelurahan Babura dengan Metode MFEP - Supiyandi, Supiyandi; Siahaan, Andysah Putera Utama; Alfiandi, Alfiandi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
The employee is a person who works at the company with a predetermined time and also with a fixed salary as well. Honorary employees have fewer facilities than employees but. A company is not responsible for providing various traditional employer benefits, including taxes, social security and workers' compensation. Like a wise in the village office of Babura, each village office has a number of temporary employees to help work from the village office, including in Babura village office. This village also has several people as honorarium employees. In a certain period, employee salaries will change and will be replaced by new people. But to choose employee salaries cannot also be done easily. There are several requirements that must be met so that the prospective employee is well received. Several criteria will be taken into account in the selection process for prospective employee employees. Decision support systems are a good method of determining which employees are appropriate or not. The Multifactor Evaluation Process (MFEP) method can assist the Babura village office in determining who will be selected to be an honorarium employee at the office. By applying this method, the Babura village office will be greatly helped in assessing prospective employee salaries to be employed in the village office